(untitled) (Sebha University Conference Proceedings, 2022)
This study aims to know the role of work ethics in combating administrative corruption, this study was applied to a random sample (50) employees of the Public Administration of Sebha University, and the main question of this study was represented in the following question: What is the role of work ethics in combating administrative corruption at Sebha University? The researcher chose the field study, and the data were collected by means of a questionnaire, and the data obtained were analyzed by the Statistical Package for Social Sciences (SPSS).the result find out Statistical significance between work ethics and administrative corruption in the public administration, where the correlation coefficient reached (-0.634) with a statistical significance at a significant level (0.01), that employees of the public administration of Sebha University have a high level of work ethics, where the general arithmetic average reached (3.24) with a standard deviation (0.77), which is greater than the average used in the study, Public Administration Sebha University have a low level regarding the dimension of administrative corruption for most of its paragraphs, where the average answer It (2.9487) and the standard deviation (0.8323), this may be attributed to the wages that workers receive is not suitable for them, workers accept the gift offered to them in order to complete transactions quickly, workers do activities other than this job during official working hours. Employees refused to take orders from officials, employees refused to take responsibility such as signing documents.